Ancient History in the Qur'an: Images and Scenes from Ancient Egypt and Mesopotamia - BOUMAKEL, Moulay Elhadj Ahmed (Journal of Ecohumanism, 2026)
This study examines the images and scenes related to ancient Egypt and Mesopotamia in the Qur’an, focusing on the way Qur’anic narratives refer to historical settings, figures, peoples, places, and civilizational features connected with these two regions. The corpus of the study consists of Qur’anic verses associated with ancient Egypt and Mesopotamia, including direct references to Egypt and Babylon as well as indirect narrative references linked to the nemes of figures, rulers, communities, and events. The study adopts a descriptive, analytical, and comparative method: it first identifies and classifies the relevant Qur’anic material, then analyzes its thematic content, and finally compares it with classical historical sources and modern historical and archaeological studies. The main result is that classical and archaeological evidence does not provide detailed confirmation of all Qur’anic stories, events, and figures. However, this evidence does not contradict the broader civilizational environment reflected in the Qur’anic narratives, particularly the centralization of political authority, the role of rivers and agriculture, religious and social complexity, and the advanced urban development of ancient Egypt and Mesopotamia.